Identificação de contingências e princípios da performance management através de relatos verbais de gestores de recursos humanos e colaboradores de empresas da cidade de São Paulo - Bernardo, Alexandre José (2011)
The behavioral analysis studies human behavior in various situations. Performance Management is a proposal for intervention based on scientific principles supported by this line of research. It can be defined as a functional system, where relations act as stimuli or consequences of workers' behaviors are closely interwoven, in which positive reinforcement can play an important role in controlling the behavior and the handling of the punishment. The proposed Performance Management, through its basic precepts, conveys that some behavioral principles act as facilitators in achieving a desired outcome. This study is aimed to identify contingencies and behavioral principles through the verbal report of human resource managers and company workers in São Paulo. The participants were two professionals in human resources from two different companies in the city of São Paulo working as industry representatives. This experiment was performed simultaneously with an application of 120 questionnaires, given to officials of the companies who belonged to the professionals in RH. The return of the questionnaires was 65%, completing the study with 78 workers. The aim of this study was to identify contingencies and the principles of Performance Management across the verbal report of human resource managers and employees of these companies. The results were as follows. In practical terms, there is a widespread ignorance on the part of managers regarding the principles pointed out by Daniels and Daniels (2006), identified in the introduction to this research. It can be seen that some principles are used in day-to-day business, but such use is due to an ancient cultural practice, not actually assigned to a technical or received by the manager. On the other hand, it can be seen that the discourse of personnel managers in business will identify many of the rules between them, although these are not completely compatible with the proposals of Performance Manager. It is believed that studies regarding the applicability of behavioral principles coupled with intervention projects in everyday organizations can promote knowledge and use intentional rational principles, which were studied here. Finally, it was noted that the discourse of the organization offers a way to implement the stipulations of PM. This will probably not be an easy path, even through the distance that was found between what was proposed by Daniels and Daniels (2006), and data collected in organizations